PENGARUHGAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA - Zarmaili Zarmaili (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
Leadership style (the style manager) is one part of an organization that had a major influence and a major determinant of the internal environment of an organization. Because of the style of Leadership will determine how organizations operate, how he formed personality (personality), how it affects the environment and how it affects the Organization's information systems. An organization can perform activities well and was clearly on the basis of keputusasn the right and true leader. The leader of the memiliiki a force (power) in determining the attitude to make a decision at the discretion of the organization.This article sets forth do kepemimpinanberpengaruh style against work productivityemployees in government institutions the province of Jambi. Study of the qualitative approach uses the libraries in getting data to build the secondary data. The data obtained through direct interviews with 50 respondents representing the SEGWAY in the scope of the provincial Government of Jambi. This study reveals the form of leadership style that developed in the Government of the province of Jambi and pangaruhnya against work productivity employees starting in 2000 until the year 2010. In the paper that outlines how important leadership style to enhance the productivity of the employees work in order to realize the goals of an organization. This paper is useful for leaders and employees to understand and get to know how the right leadership style for an organization he leads. In addition, for the researchers and studentscan take advantage of this paper as a reference in the explore leadership style.keyword : style, leadership, performance